Analysis of Law Enforcement on the Case of THTI TNI Soldiers at the Medan Military Court - Gurning, Romiduk; Zulyadi, Rizkan; Ramadhan, M. Citra (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the legal regulation and law enforcement against the crime of absenteeism without permission (THTI) carried out by TNI soldiers at the Medan Military Court, as well as the relationship between the Military Criminal Code (KUHPM) and the Criminal Code (KUHP). The research methods used are normative juridical and empirical juridical, with legislative, case, and conceptual approaches, as well as data collection through document studies and interviews. The results of the study show that legal arrangements related to THTI have been comprehensively regulated in Article 87 of the Criminal Code, with sanctions aimed at maintaining military discipline. Law enforcement against the THTI case at the Medan Military Court is carried out through the stages of investigation, investigation, prosecution, and execution of the verdict. The relationship between the Criminal Code and the Criminal Code reflects the principle of lex specialis derogat legi generali, where the Criminal Code is prioritized for TNI soldiers. However, there are challenges in determining jurisdiction in cases involving civil society, so coordination between military courts and general courts is needed. This study recommends increasing the socialization of the rule of law to soldiers, strengthening the capacity of military legal officers, and moral development to prevent THTI violations. With this step, it is hoped that the handling of THTI cases can run more effectively and fairly in accordance with the principles of military law and general criminal law.